2022
DOI: 10.3390/fermentation8100496
|View full text |Cite
|
Sign up to set email alerts
|

Lacticaseibacillus paracasei KC39 Immobilized on Prebiotic Wheat Bran to Manufacture Functional Soft White Cheese

Abstract: In the current study, probiotic Lacticaseibacillus paracasei KC39 was immobilized on wheat bran as a carrier. The immobilized synbiotic biocatalyst was freeze-dried and used as an adjunct during the production of functional soft white cheese. Free freeze-dried Lc. paracasei cells as an adjunct and a control cheese with a commercial starter were used for comparison. In addition to a fiber content of 1.12%, the functional cheese made using the synbiotic biocatalyst showed higher cell viabilities in the gastric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
6
3
0
Order By: Relevance
“…These results are in accordance with previous studies that demonstrated the enhancement of cell survival by cell immobilization [4,32,33]. Indeed, the incorporation of immobilized L. casei ATCC 393 on apple pieces and casein in yogurt resulted in cell loads > 7 logcfu/g up to 28 days of storage [32], while Shehata et al (2022) reported that soft cheese with immobilized L. paracasei cells on wheat bran exhibited high cell loads (>7.5 logcfu/g) after 30 days of storage [33]. Of note, a significant increase in lactobacilli numbers was observed up to 3 days of storage, which may be attributed to the ability of lactobacilli to adapt well to the milk environment [32].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results are in accordance with previous studies that demonstrated the enhancement of cell survival by cell immobilization [4,32,33]. Indeed, the incorporation of immobilized L. casei ATCC 393 on apple pieces and casein in yogurt resulted in cell loads > 7 logcfu/g up to 28 days of storage [32], while Shehata et al (2022) reported that soft cheese with immobilized L. paracasei cells on wheat bran exhibited high cell loads (>7.5 logcfu/g) after 30 days of storage [33]. Of note, a significant increase in lactobacilli numbers was observed up to 3 days of storage, which may be attributed to the ability of lactobacilli to adapt well to the milk environment [32].…”
Section: Discussionsupporting
confidence: 93%
“…The incorporation of immobilized probiotic cells resulted in higher cell viability compared to the cheese sample fortified with free cells, indicating the positive impact of cell immobilization on the maintenance of high cell loads. These results are in accordance with previous studies that demonstrated the enhancement of cell survival by cell immobilization [4,32,33]. Indeed, the incorporation of immobilized L. casei ATCC 393 on apple pieces and casein in yogurt resulted in cell loads > 7 logcfu/g up to 28 days of storage [32], while Shehata et al (2022) reported that soft cheese with immobilized L. paracasei cells on wheat bran exhibited high cell loads (>7.5 logcfu/g) after 30 days of storage [33].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations